Chronic consumption of a high‐fat diet rich in corn oil activates intrinsic cell death pathway and induces several ultrastructural changes in the atria of healthy and type 1 diabetic rat. (10th September 2019) - Eid, Refaat A.; Eleawa, Samy M.; Alkhateeb, Mahmoud A.; Aldera, Hussain; Zaki, Mohamed Samir Ahmed; Al‐Shraim, Mubarak; Saeed, Mansour A.; El‐kott, Attalla Farag; Alaa Eldeen, Muhammad; Alassiri, Mohammed; Alshehri, Majed M.; Salem Al‐Shudiefat, Abd Al‐Rahman; et al.
Abstract: This study investigates the effect of chronic consumption of a high‐fat diet rich in corn oil (CO‐HFD) on atrial cells ultrastructure, antioxidant levels and markers of intrinsic cell death of both control and type 1 diabetes mellitus (T1DM)‐induced rats. Adult male rats (10 rats/group) were divided into four groups: control fed standard diet (STD) (3.82 kcal/g, 9.4% fat), CO‐HFD (5.4 kcal/g, 40% fat), T1DM fed STD, and T1DM + CO‐HFD. CO‐HFD and T1DM alone or in combination impaired systolic and diastolic functions of rats and significantly reduced levels of GSH and the activity of SOD, enhanced lipid peroxidation, increased protein levels of P53, Bax, cleaved caspase‐3, and ANF and decreased levels of Bcl‐2 in their atria. Concomitantly, atrial cells exhibited fragmentation of the myofibrils, disorganized mitochondria, decreased number of atrionatriuretic factor (ANF) granules, and loss of gap junctions accompanied by changes in capillary walls. Among all treatments, the severity of all these findings was more severe in T1DM and most profound in the atria of T1DM + CO‐HFD. In conclusion, chronic consumption of CO‐HFD by T1DM‐induced rats elicits significant biochemical and ultrastructural damage to rat atrial cells accompanied by elevated oxidative stress and mitochondria‐mediated cell death.